Comparison of airflow, coal combustion, NOx emissions, and slagging characteristics among three large-scale MBEL down-fired boilers manufactured at different times. (1st February 2017) - Ling, Zhongqian; Ling, Bo; Kuang, Min; Li, Zhengqi; Lu, Ye
Highlights: Cold-modeling airflow and industrial-size experiments were performed for three MBEL down-fired boilers. Flow-field deflection, asymmetric combustion, NO x emissions, and slagging status varied greatly among them. An appropriate parameter setup was recommended for new designs of MBEL down-fired boilers. Abstract: Boilers manufactured by using the down-fired technology of British Mitsui Babcock Energy Limited Corp. (called as MBEL down-fired boiler) account for an about 20% Chinese down-fired boiler's market share. The published work showed that MBEL down-fired boilers suffered similarly from problems of asymmetric combustion and high NO x emissions, while combustion status and burnout rate varied greatly among boilers manufactured at different times. To uncover the airflow, coal combustion, NO x emissions, and slagging characteristics with respect to various boiler's parameters (including furnace configuration, burner layout pattern, and air-distribution model), cold-modeling airflow experiments and full-load industrial-size experiments under design parameters were performed for three typical MBEL down-fired boilers (with a boiler capacity of 350, 300, and 600 MWe, respectively). All boilers present flow-field deflection, with the downward airflow in one side penetrating much deeper than that in the other side. Consequently, asymmetric combustion appears in real operations, with large gas temperature gaps existing between the front- and rear-half furnace sides. The 350 MWe boiler, which has a leptosome furnace pattern and owns the highest secondary-air velocity and volumetric heat capacity, shows the weakest flow-field deflection and highest furnace gas temperature levels corresponding to the lowest burnout loss, but unfortunately, suffers from particularly high NO x emissions and serious furnace-arch slagging. On the contrary, the 300 MWe boiler generates the lowest gas temperature levels and NO x emissions and highest burnout loss, without such a slagging problem that appearing in the 350 MWe boiler. Although the 600 MWe boiler also presents a poor furnace performance, its combustion status, gas temperatures, and burnout rate are all a little better than those of the 300 MWe boiler, with the exception of higher NO x emissions and the deduced furnace-arch slagging problem. Finally, the three boilers' performance comparison generates an appropriate parameter assemble recommended for new MBEL down-fired boiler designs.